2019
DOI: 10.3390/electronics8060645
|View full text |Cite
|
Sign up to set email alerts
|

Electric Double Layer Field-Effect Transistors Using Two-Dimensional (2D) Layers of Copper Indium Selenide (CuIn7Se11)

Abstract: Innovations in the design of field-effect transistor (FET) devices will be the key to future application development related to ultrathin and low-power device technologies. In order to boost the current semiconductor device industry, new device architectures based on novel materials and system need to be envisioned. Here we report the fabrication of electric double layer field-effect transistors (EDL-FET) with two-dimensional (2D) layers of copper indium selenide (CuIn 7 Se 11 ) as the channel material and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…As grown CIS crystal has black mica-like texture. Layered CIS has been characterized by SEM, HRTEM, EDX, and XRD. The ratio between copper and indium has been found to be 1:7, which is consistent with layered-phase formation in CIS (CuIn 7 Se 11 ).…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…As grown CIS crystal has black mica-like texture. Layered CIS has been characterized by SEM, HRTEM, EDX, and XRD. The ratio between copper and indium has been found to be 1:7, which is consistent with layered-phase formation in CIS (CuIn 7 Se 11 ).…”
Section: Methodssupporting
confidence: 56%
“…Multielemental compounds bring an extra degree of freedom via stoichiometric variations, and varying elemental composition could play an important role in determining physical properties. , For example, our own investigations suggest that incorporating copper in indium selenide (InSe) in order to get layered ternary systems of copper indium selenide (CuIn 7 Se 11 ) and using them as the active component for photodetection can substantially improve a photodector’s figures of merit (for example, response time) . Despite the fact that CIS-based systems show excellent electronic , and optoelectronic , properties, electron transport in these systems is not well understood. In order to further engineer their properties for various device applications, it is crucial to understand the nature of electron transport in these materials.…”
mentioning
confidence: 99%
“…At a fixed source–drain voltage ( V DS ) of 3 V, source–drain currents ( I DS ) first slightly decreased and then increased when gate voltages ( V G ) increased from −50 to 50 V. This showed that the CIS nanoflakes exhibited n‐type semiconductive behavior and good switching characteristics with an approximate on/off ratio of 10 9 , which was much higher than that of CuIn 7 Se 11 and better or comparable with those of other as‐grown 2D materials. [ 28,42–46 ] Because graphene exhibits metallic behavior, the field effect mobility of the CIS nanoflakes can be calculated through the transfer curves of the devices according to the following equation: μ =LW dεεnormalr1VDSdIDSdVnormalG where L and W are the channel length and width of the device, ε (= 8.85 × 10 −12 F m −1 ) is the vacuum permittivity, ε r (= 3.9) is relative permittivity of the insulating barrier SiO 2 , and d (= 300 nm) is the thickness of SiO 2 . The field effect mobility of the CIS nanoflakes was estimated to be 30.4 cm 2 V −1 s −1 , which was comparable with that of mechanically exfoliated CuIn 7 Se 11 .…”
Section: Resultsmentioning
confidence: 99%
“…−50 to 50 V. This showed that the CIS nanoflakes exhibited n-type semiconductive behavior and good switching characteristics with an approximate on/off ratio of 10 9 , which was much higher than that of CuIn 7 Se 11 and better or comparable with those of other as-grown 2D materials. [28,[42][43][44][45][46] Because graphene exhibits metallic behavior, the field effect mobility of the CIS nanoflakes can be calculated through the transfer curves of the devices according to the following equation:…”
Section: Resultsmentioning
confidence: 99%
“…With the advent of layered Van der Waals solids [1][2][3] and the envisioned applications that are being expected [4][5][6][7][8][9][10][11][12][13] has led to a large variety of fundamental as well as applied scientific investigations. Among these investigations, many have shown that intrinsic properties of 2D layered materials are strongly dependent on the number of layers [8,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%